LEVANTAMENTO DE MACROFUNGOS NA TERRA INDÍGENA PORTO LINDO (JAKAREY), MUNICÍPIO DE JAPORÃ-MS. - VILHARVA, Aloizio; GUIMARÃES, Felipe da Silva; DIAS, Rosa Maria; KASHIWAQUI, Elaine Antoniassi Luiz; ABELHA, Milza Celí Fedatto (ANAIS DO ENIC, 2025)
-